Policy borrowing in vocational education and training (VET) : VET system typologies and the "6 P strategy" for transfer analysis - Pilz, Matthias [Verfasser] (My University, 2017)
"The issue of exporting VET systems is currently very topical in the international debate. It is, however, surprising that there is virtually no recent research into such areas as practicability, successes achieves, problems encountered, and long-term impact. If a transfer approach should be successful, there must be at a first stage a comprehensive and detailed analysis of the diverse needs and perspectives of the local stakeholder groups. In line with this logic, the paper presents an analytic tool that can be used to categorize individual countries in terms of the way VET is perceived and designed within the specific socio-cultural context. This also enables initial indicators of potential needs to be identified. The next stage in the paper is, to focus on the actual transfer of all or part of a VET system from one country to another. There has so far been no adequate explanation of how this might be done. The existing empirical findings show that transfer is a major challenge for all those involved. The approach is intended to provide a structure for that transfer and identify possible problems or obstacles before the process get under way. This approach, labelled as the '6 P strategy', is based on the findings documented in the literature and supplemented with author's experience of a range of transfer projects." (Authors' abstract, BIBB-Doku)
Keywords: S System beruflicher Bildung; I 1 Internationale Berufsbildung; I 1.1 Systemberatung; Berufsbildung; Berufsbildungssystem; Internationale Zusammenarbeit; Bildungstransfer; Typologie